Enhanced Electrochemical and Thermal Stabilities of Li[Ni0.88Co0.09Al0.03]O2 Cathode Material by La4NiLiO8 Coating for Li–Ion Batteries. Issue 9 (14th April 2020) - Zhang, Ruixin; Wang, Yangyang; Song, Xiang; Li, Guoran; Liu, Sheng; Gao, Xueping
Abstract: Nickel‐rich layered oxides with high reversible capacity are considered as the next‐generation cathode materials for lithium‐ion batteries (LIBs). However, capacity degradation induced by side reactions and structural degradation on the surface has been the main obstacle for their applications. In this work, a stable layer of La4 NiLiO8 is coated on Ni‐rich material of Li[Ni0.88 Co0.09 Al0.03 ]O2 (NCA) by a facile method. The formation process of the La4 NiLiO8 layer is analyzed from both thermodynamic and dynamics aspects. The results indicate that oxygen migration evolution near the NCA surface is effectively reduced, thus improving the structural stability of the lattice and alleviating the side reactions on the surface. The electrochemical and thermal stabilities of NCA material are remarkably improved by coating the La4 NiLiO8 layer. This work provides a strategy for effective coating functional materials on Ni‐rich cathode materials for LIBs. Abstract : Put your coat on : The formation process of the La4 NiLiO8 coating layer on Ni‐rich oxide is thermodynamically and kinetically driven, resulting in enhanced electrochemical and thermal stabilities for lithium‐ion batteries.